Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from Marcus G. Langseth in the Arctic Ocean, Bering Sea and others from 2011-04-13 to 2011-12-28 (NCEI Accession 0144305) ... - Takahashi, Taro; Sweeney, Colm; Sutherland, Stewart C. (NOAA National Centers for Environmental Information, 2016)
This dataset includes Surface underway data collected from Marcus G. Langseth in the Arctic Ocean, Bering Sea, Chukchi Sea, Gulf of Alaska, Hawaiian Islands Humpback Whale National Marine Sanctuary and North Pacific Ocean from 2011-04-13 to 2011-12-28. These data include BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY and SEA SURFACE TEMPERATURE. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Stewart C. Sutherland and Taro Takahashi of Lamont-Doherty Earth Observatory (LDEO) and Colm Sweeney of NOAA Earth System Research Laboratory (ESRL) as part of the VOS_Marcus_Langseth_Lines_2011 dataset. CDIAC associated the following cruise ID(s) with this dataset: 33H320110413 ...